Secondary alveolar bone grafting of clefts using bioactive glass 45S5: Long-term dental and periodontal status - Verdier, Emmanuelle; Azzis, Olivier; Marchand, Mathilde; Jeanne, Sylvie; Lebullenger, Ronan; Gatibelza, Marie Eve; Davit-Béal, Tiphaine; Brézulier, Damien (American journal of orthodontics and dentofacial orthopedics, 2025)
Secondary alveolar bone grafting (SABG) restores the continuity of alveolar bone in orofacial clefts to establish a functional dental occlusion. Given the complications of autografts, the use of biomaterials has been proposed. In a previous study, we demonstrated 3-dimensional radiographic success at 1 year of >80% when bioactive glass 45S5 was used. The aim was now to establish the clinical success rate of SABG made with bioactive glass based on a combination of dental and periodontal criteria after 5 years. This retrospective cohort study included patients who underwent SABG between 2015 and 2021 and were born before 2012. A total of 45 SABG on 35 patients was included. The mean surgical follow-up period was 5.75 years. Clinical success was defined according to a composite outcome that took into account the periodontal volume (normal or depression) at the graft level and the recession on the adjacent teeth (no recession or Miller Class I). It was studied using descriptive statistics. Subgroup analysis according to lateral incisor status and space management was performed by Fisher exact test. The clinical success rate was 71.1%. Neither the absence of a tooth close to the cleft (P = 0.845) nor the opening or closing of the space (P = 0.325) in the case of a missing tooth influenced the outcome of the procedure. Furthermore, an association was only found between radiographic and clinical success in the subgroup without missing teeth (P = 0.035). It was not found for the full cohort (P = 0.061) nor the group with missing teeth (P = 0.299). The use of bioactive glass 45S5 instead of autograft is relevant for SABG, with a 5-year clinical success rate of >71%. A complete dental formula allows for a more predictable result. •Bioactive glass 45S5 is relevant for SABG, with a 5-year periodontal success rate of over 71%.•Absence of lateral incisor does not correlate with clinical periodontal success.•Space management in missing lateral cases, does not influence clinical periodontal success.•Without missing lateral, long-term clinical success is linked to radiographic success at 2 years.